Prospective 12-month functional and vocational outcomes of hip arthroscopy for femoroacetabular impingement as part of an evidence-based hip pain rehabilitation pathway in an active military population. Issue 1 (9th August 2016) - Bennett, A N; Nixon, J; Roberts, A; Barker-Davies, R; Villar, R; Houghton, J M
Abstract : Background: Femoroacetabular impingement (FAI) is common with an estimated prevalence of 10–15% among young active individuals. The natural history of the disorder is progression to early osteoarthritis. Hip arthroscopy is recommended if conservative treatments fail; however, outcomes are unclear, particularly in highly active populations. Aim: To evaluate the functional and vocational outcome of hip arthroscopy, as part of an evidence-based rehabilitation hip pain pathway, for the treatment of FAI in an active military population. Methods: All patients in the defence rehabilitation hip pain pathway, with a confirmed diagnosis of FAI who failed conservative treatment, were assessed prior to surgery and at 2, 6 and 12 months postsurgery. Outcome measures included the Visual Analogue Scale (VAS) for hip pain, Non-Arthritic Hip Score (NAHS) for function, and vocational assessments including functional activity assessment (FAA) and Joint Medical Employment Standard for military employability and deployability. Results: 101 patients completed the study (mean age=33 years) (male:female:75:26) (Royal Navy/British Army/Royal Air Force: 13%/48%/39%). Outcomes demonstrated significant improvements with large effect size. Preoperative NAHS mean=62.9 (SD 16.4), 12-month postoperative NAHS mean=78.8 (18.3), mean improvement in NAHS=15.9 (95% CI 12.3 to 19.5, p<0.001). Preoperative VAS pain mean=51.3 (20.9), 12-month postoperative VAS pain=25.6 (24.5). Mean improvement 25.7 (95% CI 19.4 to 31.99, p<0.001). 73% of patients had a deployable medical category at 12 months postoperative. Conclusions: These data confirm that hip arthroscopy as part of a structured evidence-based multidisciplinary care pathway produces significant and continued symptomatic, functional and vocational improvements over a 12-month period in a military population exposed to high intensity, weight-bearing exercise in uncontrolled and unforgiving environments.